IMPLEMENTASI METODE LEAN SIX SIGMA SEBAGAI UPAYA MEMINIMALISASI CACAT PRODUK KEMASAN CUP AIR MINERAL 240 ml (STUDI KASUS PERUSAHAAN AIR MINUM) - Ari Fakhrus Sanny; Mustafid Mustafid; Abdul Hoyyi (Jurnal Gaussian, 2015)
Efforts to increase productivity can not be said that the human factor is not the only factor which should be observed, studied, analyzed, and repaired in the effort to increase productivity, but also other factors such as machine, equipment, raw materials, factory buildings, etc. may also affect the productivity improvement efforts remain to be considered. Quality is the customer's main factor to decide products and services. Therefore, quality is a key factor which brings business success and growth, and improves competitive position. Lean six sigma method is a method to identify and eliminate waste or activities which are not value added and analyze defect rate product approaches zero defect products. This study aims to implement lean six sigma methods in quality control with case studies of product quality bottled water cup 240 ml at the quality control process produces eleven types of disabilities. Efforts should be made to improve the quality of products, one of them by monitoring the production process control diagram. The results obtained in this study is the value of DPMO on line 1 of 546 machines produce sigma level of 4.766 and a percentage of 99.95%, which means that in a million products cup 240 ml mineral water contained 0.05% units of a product that does not fit in production line machine 1. The DPMO values on line 2 of 291 machines produce sigma level of 4.932 and a percentage of 99.97%, which means that in a million products cup 240 ml mineral water contained 0.03% units of a product that does not fit in production line machine 2. Keywords : Quality, Quality Control, Lean Six Sigma